Marion Lane and the raven's revenge [large type] - Willberg, T. A. (Willberg, T. A. Marion Lane (Series), 2023)
"London, 1960. Marion Lane, a twenty-five-year-old apprentice detective at the elusive Miss Brickett's Investigations & Inquiries, is busier than ever and determined to prove herself worthy of an official Inquirer badge. But when her close friend's girlfriend, Darcy, is targeted by a dangerous gang leader and seeks out the Inquirers' assistance, Marion cannot help but get involved. Just when Marion thinks she has the situation under control, Darcy disappears and the agency receives a package containing a dead raven. Everyone is puzzled by what the threat could mean, except for Marion. She recognizes it as the same calling card left on her mother's doorstep just before she died. With harrowing twists and turns, Marion Lane and the Raven's Revenge follows Marion's most personal case to date. To uncover who is behind these ominous packages and find Darcy, she must piece together how they are related to her mother's mysterious death and secretive past"--